(untitled) (Research, Society and Development, 2023)
Tuberculosis is an infectious and contagious disease, with high incidence and prevalence rates, and associated with low socioeconomic conditions. In this scenario, Primary Health Care (PHC), as care coordinator, must be able to promote comprehensive actions, aiming to improve the quality of life and effectively control the disease. However, there are still several challenges in the care of these patients. Therefore, this study aims to identify the challenges in nursing care for patients with tuberculosis in primary care. This is an integrative literature review, carried out in July and August 2023, using the Health Sciences Descriptors (DeCS): "Tuberculosis", "Primary care" and "Nursing". 127 articles were found and, after a careful selection, 12 articles were used to compose this research. From the studies found, it is evident that the main challenges in caring for patients with TB involve lack of knowledge, lack of access, low financial conditions, lack of accessibility, absence and high turnover of professionals, lack of incentives and stigmatizing behaviors. In view of this, it is important that the care for patients with tuberculosis involves the user, professionals, the family, the management of health services and is articulated with other sectors, so that their needs are resolute, and that such challenges are overcome.